Decoupling Office Energy Efficiency From Employees' Well-Being and Performance: A Systematic Review - Kozusznik, Malgorzata W.; Maricutoiu, Laurentiu Paul; Peiró, José M.; Vîrgǎ, Delia Mihaela; Soriano, Aida; Mateo-Cecilia, Carolina (Frontiers in Psychology, 2019)
Energy efficiency (i.e., the ratio of output of performance to input of energy) in office buildings can reduce energy costs and CO2 emissions, but there are barriers to widespread adoption of energy efficient solutions in offices because they are often perceived as a potential threat to perceived comfort, wellbeing and performance of office users. However, the links between offices’ energy efficiency and users’ performance and well-being through their moderators are neither necessary nor empirically confirmed. The purpose of this study is to carry out a systematic review to identify the existing empirical evidence regarding the relationships between energy-efficient solutions in sustainable office buildings and the perceptions of employees’ productivity and wellbeing. Additionally, we aim to identify relevant boundary conditions for these relationships to occur. A systematic literature search of online databases for energy efficiency literature (e.g., Environment Complete, GreenFILE), employee literature (e.g., PsycINFO, Business Source Complete) and general social science literature (e.g., Academic Search Complete) yielded 34 empirical studies. Also, inclusion and exclusion criteria were set. The results suggest that it is possible to decouple energy costs from organizational outcomes such as employee well-being and performance. Also, they indicate the existence of moderators and mediators in the relationship between green office building solutions and wellbeing/performance. Directions for future research and the implications for practice considering different stakeholders interested in implementing green building solutions, adopting energy-saving measures in offices, and improving employees’ functioning are suggested.